Quality Characteristics of Boba Pearls from Honey Sweet Potato (Ipomoea batatas L. Var. Madu) Flour and Tapioka - Nurud Diniyah; Anggun Fitria Mustika Yekti; Asmak Afriliana; Giyarto Giyarto; Achmad Subagio (Universitas Sebelas Maret (UNS), 2025)
Boba made from tapioca tends to have a slightly rough, firm, and dense texture. Substituting honey sweet potato flour as a source of sweetener, natural coloring, and low starch content can improve the structure and enhance the quality of the boba. This research aims to determine the effect of the ratio of honey sweet potato flour and tapioca on physical, chemical, and sensory quality characteristics, as well as to determine the best treatment for boba with honey sweet potato flour and tapioca. This research used a Completely Randomized Design (CRD) with one treatment factor, namely the ratio of honey sweet potato flour and tapioca (0:100, 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20, 90:10 and 100:0) in triplicate. The made pearls were subjected to physical (diameter, bulk density) analysis, texture profile (hardness, gumminess, springiness, and chewiness) analysis, chemical (moisture content, starch content, reducing sugar content) analysis, and sensory (color, taste, aroma, and texture) evaluation. According to obtained results, the ratio of honey sweet potato flour and tapioca was significantly difference to the physical (diameter, bulk density) proprerties, texture profile (hardness, gumminess and chewiness), chemical properties (moisture content, starch content, reducing sugar content), and sensory evaluation (color, taste, aroma and texture) of boba pearl. The ratio of honey sweet potato flour and tapioca, 90:10, is the best treatment with an effectiveness value of 0.73. The characteristics of raw boba pearl as a best treatment respectively 0.92 ± 0.00 cm diameter; 0.40±0.00 g/ml bulk density and 47.45±0.58% water content, while the characteristics of ripe boba were 1.15±0.00 cm of diameter; 0.51±0.00 g/ml bulk density; 62.94±1.32 gf hardness; 103.21±1.62 gf gumminess; 53.97±2.37 gf springiness, 0.46±0.00 gf chewiness; 64.50±1.57 % water content; 11.81 ± 0.04% starch content; 30.47 ± 0.02% reducing sugar; 4.10 ± 0.79 (like) hedonic color; 4.15 ± 0.81 (like) taste; 4.05 ± 0.76 (like) aroma; and 4.05 ± 0.69 (like) texture.